PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI MADRASAH - Salim, Ahmad (IAIN Ponorogo, 2014)
Abstract: The variety of life challenge in the future and study result not yet showed by student, require government to innovate education system through curriculum change which then recognized with curriculum 2013. One of typical curriculum 2013, in course using of scientific approach for all of subject including Islamic education in madrasa. Though the truth of knowledge Islamic education in madrasa coming from non-scientific truth which refused in scientific approach system. This study about scientific approach implementation at Islamic education in madrasah. Approach implementation of Islamic education at madrasah besides giving attention to science method in general, educator have to pay attention at several things in order to optimal learning. Several things which must get attention by educator are science approach, do not eliminate the truth of dogmatic to the truth of empiric, the importance of theme integration which the truth of dogmatic with pure science, repeat description about competition standard of Islamic education at madrasa, the importance of creativity development and educator innovation in learning process.Â Ù ÙØ®Øµ: ØªÙÙÙØ¹ ØªØØ¯ÙØ§Øª ØÙØ§Ø© Ø§ÙÙØ§Ø³ Ø§ÙØ¥ÙØ¯ÙÙÙØ³ÙÙÙ ÙÙ Ø§ÙÙ Ø³ØªÙØ¨Ù ÙØ¸Ø§ÙØ±Ø© ÙØªØ§Ø¦Ø¬ Ø§ÙØªØ¹ÙÙ Ø§ÙØ³ÙØ¦Ø© ÙØ¯Ù Ø§ÙØ·ÙØ§Ø¨ Ø§ÙØªØ¶Øª Ø§ÙØÙÙÙ Ø© ÙØªØ¬Ø¯ÙØ¯ Ø§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ Ø¨ØªØºÙÙØ± Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³ÙØ ÙÙØ³Ù Ù Ø§ÙØ¬Ø¯ÙØ¯ Ø¨Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù 2013. ÙÙ Ù Ù Ù ÙØ²Ø§Øª ÙØ°Ø§ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¬Ø¯ÙØ¯ ÙÙ Ø§Ø³ØªØ¹Ù Ø§Ù Ø§ÙÙ Ø¯Ø®Ù Ø§ÙØ¹ÙÙ Ù ÙÙ ØªØ¯Ø±ÙØ³ Ø¬Ù ÙØ¹ Ø§ÙÙ ÙØ§Ø¯ ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ ÙÙÙÙØ§ ØªØ¹ÙÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©Ø Ù Ø¹ Ø£Ù ØµØØ© Ø§ÙÙ Ø¹Ø§Ø±Ù ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§Ø¹ØªÙ Ø¯ ÙØ«ÙØ±Ø§ Ø¹ÙÙ Ø§ÙØµØØ© ØºÙØ± Ø§ÙØ¹ÙÙ ÙØ© Ø§ÙÙ Ø·Ø±ÙØ¯Ø© ÙÙ ÙØ¸Ø§Ù Ø§ÙÙ Ø¯Ø®Ù Ø§ÙØ¹ÙÙ Ù. Ø¨ØØ«Øª ÙØ°Ù Ø§ÙÙ ÙØ§ÙØ© ÙÙ ØªØ·Ø¨ÙÙ Ø§ÙÙ Ø¯Ø®Ù Ø§ÙØ¹ÙÙ Ù ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©. ÙÙ ØªØ·Ø¨ÙÙ Ø§ÙÙ Ø¯Ø®Ù Ø§ÙØ¹ÙÙ Ù ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø¨Ø¬Ø§ÙØ¨ Ø§ÙØ§ÙØªÙ Ø§Ù Ø¨Ø§ÙÙÙØ§Ø¹Ø¯ Ø§ÙØ¹ÙÙ ÙØ© Ø¹Ø§Ù Ø©Ø Ø¹ÙÙ Ø§ÙÙ Ø¯Ø±Ø³ Ø£Ù ÙÙØªÙ Ø¨Ø¨Ø¹Ø¶ Ø§ÙØ£Ù ÙØ± ÙÙØ³ÙØ± Ø§ÙØªØ¯Ø±ÙØ³ Ø³ÙØ±Ø§ Ø¬Ù ÙÙØ§. ÙÙØ°Ù Ø§ÙØ£Ù ÙØ± ÙÙ Ø£Ù Ø§ÙÙ Ø¯Ø®Ù Ø§ÙØ¹ÙÙ Ù ÙØ§ ÙÙÙØµ Ø£Ù ÙØ§ ÙØ²ÙÙ Ø§ÙØµØØ© Ø§ÙØ¹ÙØ¯ÙØ© Ø¥ÙÙ Ø§ÙØµØØ© Ø§ÙØ§Ù Ø¨ÙØ±ÙØ³ÙØ©Ø ÙØ£ÙÙ ÙØ© Ø§ÙØ¬Ù Ø¹ Ø¨ÙÙ Ø§ÙÙ ÙØ¶ÙØ¹ Ø§ÙØ°Ù ÙÙ ØµØØ© Ø¹ÙØ¯ÙØ© ÙØ¨ÙÙ Ø§ÙØ¹ÙÙ ÙØ© Ø§ÙØ¨ØØªØ©Ø ÙØ¥Ø¹Ø§Ø¯Ø© Ø§ÙØ¹Ø±Ø¶ Ø¹Ù Ù Ø¹ÙØ§Ø± Ø§ÙÙÙØ§Ø¡Ø§Øª ÙÙ Ù Ø§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©Ø ÙØ£ÙÙ ÙØ© ØªÙÙ ÙØ© Ù ÙØ§Ø±Ø§Øª Ø§ÙÙ Ø¯Ø±Ø³ ÙÙÙØ§Ø¡Ø§ØªÙ ÙØªØ¬Ø¯ÙØ¯Ø§ØªÙ ÙÙ Ø¹Ù ÙÙØ© Ø§ÙØªØ¹ÙÙÙ .Â Keyword: Pendekatan saintifik, pelajaran PAI, madrasah